Haemophilus influenzae carriage and antibiotic resistance profile in Belgian infants over a three-year period (2016–2018) - Ekinci, Esra; Willen, Laura; Rodriguez Ruiz, Juan Pablo; Maertens, Kirsten; Van Heirstraeten, Liesbet; Serrano, Gabriela; Wautier, Magali; Deplano, Ariane; Goossens, Herman; Van Damme, Pierre; Beutels, Philippe; Malhotra-Kumar, Surbhi; et al. (Frontiers in Microbiology, 2023)
Background: Non-typeable Haemophilus influenzae has become increasingly important as a causative agent of invasive diseases following vaccination against H. influenzae type b. The emergence of antibiotic resistance underscores the necessity to investigate typeable non-b carriage and non-typeable H. influenzae (NTHi) in children. Methods: Nasopharyngeal swab samples were taken over a three-year period (2016-2018) from 336 children (6-30 months of age) attending daycare centers (DCCs) in Belgium, and from 218 children with acute otitis media (AOM). Biotype, serotype, and antibiotic resistance of H. influenzae strains were determined phenotypically. Mutations in the ftsI gene were explored in 129 strains that were resistant or had reduced susceptibility to beta-lactam antibiotics. Results were compared with data obtained during overlapping time periods from 94 children experiencing invasive disease. Results: Overall, NTHi was most frequently present in both carriage (DCC, AOM) and invasive group. This was followed by serotype ‘f’ (2.2%) and ‘e’ (1.4%) in carriage, and ‘b’ (16.0%), ‘f’ (11.7%), and ‘a’ (4.3%) in invasive strains. Biotype II was most prevalent in all studied groups, followed by biotype III in carriage and I in invasive strains. Strains from both groups showed highest resistance to ampicillin (26.7% in carriage vs 18.1% in invasive group). A higher frequency of ftsI mutations were found in the AOM group than the DCC group (21.6% vs. 14.9% - p = 0.056). Even more so, the proportion of biotype III strains that carried a ftsI mutation was higher in AOM compared to DCC (50.0% vs. 26.3% - p < 0.01) and invasive group. Conclusion: In both groups, NTHi was most frequently circulating, while specific encapsulated serotypes for carriage and invasive group were found. Biotypes I, II and III were more frequently present in the carriage and invasive group. The carriage group had a higher resistance-frequency to the analysed antibiotics than the invasive group. Interestingly, a higher degree of ftsI mutations was found in children with AOM compared to DCC and invasive group. This data helps understanding the H. influenzae carriage in Belgian children, as such information is scarce.